Mastering digital transformation through business process management: Investigating alignments, goals, orchestration, and roles - Ana-Marija Stjepić; Lucija Ivančić; Dalia Suša Vugec (Journal of Entrepreneurship, Management and Innovation)
Both business process management and digital transformation are areas that have been a topic of interest for both academia and practice. Since digital transformation is the creation of new, innovative business models and/or change and improvement of the existing business model with the help of digital technologies, one could raise a question regarding the role which business process management plays in digital transformation. With the purpose of shedding some light on that, this paper presents a theoretical framework for observing the link between business process management and digital transformation. Moreover, the results of an extensive literature review and analysis with regards to the presented framework has been given. The results confirm the important role of business process management in digital transformation. However, the results also indicate the need for further research and a greater understanding of practice.